2017
DOI: 10.1111/jph.12607
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cochliobolus heterostrophus races in South China

Abstract: Cochliobolus heterostrophus is the causal pathogen of the southern corn leaf blight (SCLB). There are three known races: race O, race C and race T. To determine which C. heterostrophus races comprise the field population in southern China and to assess diversity of these strains in terms of virulence, 200 isolates from diseased plants were collected in nine provinces/municipalities. All were race O, that is, no race T or race C isolates were found. Sixty race O isolates that sporulated well were chosen for fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Previous studies have shown that the virulence of B. maydis and B. zeicola isolates is diversified and that these species have different pathotypes [13,42,44,45]. It was reported that race 3 of B. zeicola might be a mountain ecotype, favoring high humidity and cool temperature in mountain areas at high elevations [42,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the virulence of B. maydis and B. zeicola isolates is diversified and that these species have different pathotypes [13,42,44,45]. It was reported that race 3 of B. zeicola might be a mountain ecotype, favoring high humidity and cool temperature in mountain areas at high elevations [42,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering these results and the lesion types of our maize samples, most isolates of B. zeicola in Sichuan Province may belong to race 3. B. maydis is generally subdivided into four races, namely, O, T, C, and S, and among them, race O is the predominant pathogen of maize in China and the disease characterized by the appearance of elongated or fusiform lesions on the leaves of susceptible plants [44,45,50,51]. We inferred that isolates of B. maydis in Sichuan may mostly belong to race O.…”
Section: Discussionmentioning
confidence: 99%
“…The C. heterostrophus race O strains DY and WF were collected from previously identified C. heterostrophus race O library(3). A GFP coding region, GPDH promoter, and TrpC terminator were joined and constructed into a pCAMBIAth1300 plasmid(S6 Fig.)…”
Section: Methodsmentioning
confidence: 99%
“…The infection of C. heterostrophus and integral optical density (IOD) calculation were performed as described(3). SPSS 19.0 was used to analyze the significant variations among the IOD values of differential infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation